THE ROLE OF FIDUSIAN SECURITY LAWS IN PROTECTING ONLINE OJECT WHEN MAJOR SCALE OF SOCIAL RESTRICTIONS APPLY IN FROM CREDIT REMEDY CASE STUDY IN DKI JAKARTA - Jatmiko, Sugeng; Fiqri Saifulloh, Mohamad (IBLAM LAW REVIEW, 2021)
The Financial Services Authority (OJK) issued OJK Regulation (POJK) No. 11 / POJK.03 / 2020 concerning National Economic Stimulus as a Countercyclical Policy on the Impact of the Spread of Corona Virus Disease 2019 which regulates that debtors affected by the Coronavirus get credit restructuring, especially for Micro, Small and Medium Enterprises (MSMEs) in the tourism, transportation, hospitality and other sectors. One of the points is related to relaxation of postponement of installments of up to one year and a reduction in credit interest for borrowers in the informal sector, micro-businesses, workers who are paid per day and run businesses in productive fields. The problem is how the role of OJK regulations in easing Ojek Online credit? And how is the legal protection for online motorcycle taxis when the Large-Scale Social Restrictions take effect in the context of credit relief based on Law Number 42 of 1999 concerning Fiduciary Security? The method used is normative juridical research. The conclusion is the role of OJK regulations in relieving online motorcycle taxi credit, namely by calling two online motorcycle taxi transportation companies to apply for credit relief which are carried out collectively so that they can provide driver data and vehicle data such as engine numbers and numeric numbers to make submissions easier. This is in accordance with the rules for credit leniency stipulated in OJK Regulation (POJK) Number 11 / POJK.03 / 2020 concerning Economic Stimulus as a Countercyclical Policy. These online transportation drivers are included in the credit easing category for one year due to the impact of the corona virus pandemic or Covid-19.